Implementasi Sistem Penjadwalan Mata Kuliah Menggunakan Metode Algoritma Genetika Berbasis Web - Toyib Hidayat, Asep; Hakim, Lukman; Rio; M.Afif Ravanza (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The process of preparing the lecture schedule at Bina Insan University is still done semi-manually with the help of Microsoft Excel and takes days, even weeks, whereas making the schedule must be done optimally and quickly because the schedule will be used for lecture activities each semester, so that the scheduling process can be carried out effectively and efficiently, so we need an application that can simplify the scheduling process, namely a scheduling application and applying the right algorithm, one of the algorithms that can be used in scheduling applications is the Genetic Algorithm. Course scheduling is a process of allocating courses, lecturers, space and time by matching predetermined rules so that all these components can be fulfilled. Genetic Algorithms are search algorithms that are based on natural selection mechanisms and natural genetics. The results of the research are in the form of a schedule that is prepared automatically without any more clashes between times and classes to be used